A Penerapan Asas Kebebasan Berkontrak Dalam Perjanjian Jual Beli Komoditas Hasil Pertanian - Tadoe, Prisca Edelweys; Nubatonis, Orpa J; Dju Bire, Chatryen M (Law Faculty, Nusa Cendana University, 2024)
The application of freedom of contract in agricultural commodities purchase agreements is essential to creating a fair relantionship between farmes and buyers. This principle allows each parties the freedom to choose the terms and conditions of the agreement according to needs and interests, and it allow legal subjects to draft new agreemwnts that aren’t currently covered by the Civil Code. The ijon system is a method of purchasing and selling agricultural products that has never been seen. It’s to determine how freedom of contract is applied in relation to the effectiveness of agricultural commodity purchase agreements and what legal action can be taken in the event that the freedom of contract is violated in such agreements. Normative legal research is the research methodology employed. According to the result, inefficiency may have an impact on how the freedom of contract is applied in purchase agreements. This principle allow to determine the terms and conditions of the agreement without violating the law and public order, but the existence of legal ambiguity can cause ambiguity in the contents of the agreement, making it difficult and can cause disputes. There are two approaches to legal protection: repressive legal protection and preventive legal protection.